2018
DOI: 10.3390/ijerph15081659
|View full text |Cite
|
Sign up to set email alerts
|

Micronuclei in Exfoliated Buccal Cells of Children Living in a Cluster Area of Salento (Southern Italy) with a High Incidence of Lung Cancer: The IMP.AIR Study

Abstract: During the years 2014–2016 the University of Salento performed the “Impact of Air Quality on Health of Residents in the Municipalities of Cutrofiano, Galatina, Sogliano Cavour, Soleto and Sternatia” (IMP.AIR) study, an epidemiological-molecular research project aiming to evaluate early DNA damage in children living in an area of Salento with high incidence of lung cancer among the male population. One hundred and twenty-two children aged 6–8 years attending primary school were enrolled and the frequency of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Villarini et al [64] reported a mean MN frequency of 0.53 ± 0.61 MN% in 237 children living in Brescia, an Italian town located in the Po Valley, an area known to be highly polluted. Finally, 122 6-8-year-old children living in a rural area of Salento with moderate industrial activities showed a mean MN frequency of 0.49 ± 0.65 MN% [46].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Villarini et al [64] reported a mean MN frequency of 0.53 ± 0.61 MN% in 237 children living in Brescia, an Italian town located in the Po Valley, an area known to be highly polluted. Finally, 122 6-8-year-old children living in a rural area of Salento with moderate industrial activities showed a mean MN frequency of 0.49 ± 0.65 MN% [46].…”
Section: Discussionmentioning
confidence: 93%
“…The epithelial buccal cells from each child were collected by gently scraping the inner surface of both cheeks with a small-headed toothbrush as described in Idolo et al [46]. The cells were then transferred into tubes containing Saccomanno's fixative (50% ethanol, 2% polyethylene glycol, v/v; solution diluted in water and stored at 4 • C).…”
Section: Anthropometric Measurements and Biological Samplingmentioning
confidence: 99%
“…However, many of the children participating in the study were found exposed to unhealthy factors concerning the domestic environment or lifestyles. These may have contributed to the occurrence of DNA alterations in children's exfoliated buccal cells, detectable through MNC [ 31 ]. In our study, we select individuals considering health and lifestyles, in order to reduce bias in the interpretation of the data.…”
Section: Resultsmentioning
confidence: 99%
“…The BMC assay assesses DNA damage and allows consideration to being a predictive biomarker, since an increase in nuclear abnormalities has been associated with genotoxicity and cancer cases [ 29 31 ]. Although the BMC assay has been utilized to evaluate genotoxicity and cytotoxicity in the Mexican population, currently, there are no studies that evaluate the effects of air pollution in healthy young adults.…”
Section: Introductionmentioning
confidence: 99%
“…However, findings of the same type in other tissues were inconclusive. Research in a small cohort of Mexican children did not identify an association between adiposity and nuclear anomalies in the buccal epithelium, yet a more recent study in Italian children found a significant link between childhood obesity and MNi formation in the same tissue [ 39 , 40 ]. Similarly, there are discrepancies in studies of oxidative DNA damage in children with obesity; one reports positive correlations between obesity status in childhood and serum 8-OHdG, and two reports higher levels of 8-OHdG in urine samples [ 41 43 ], while the fourth study of urinary 8-OHdG and BMI in Italian children reports an inverse correlation [ 44 ].…”
Section: Introductionmentioning
confidence: 99%